OBSERVATÓRIO SOCIAL E DO TRABALHO: construindo as temáticas pobreza e trabalho no campo das Políticas Públicas - Maria Ozanira da Silva e Silva (Universidade Federal do Maranhão, 2018)
Based on the website www.gaepp.ufma.br and in a bibliographic and documental research, this article presents an overview about the Social and Labor Observatory, a mechanism created to publicize results of studies and researches developed in the context of GAEPP. It highlights its foundations, the context and its working mechanisms. The article has as objective to make an examination of the products and outcomes obtained in its five years of implementation. Based on the bimonthly Bulletin of the Observatory, the focus of the reflections and problematizations are the thematic axes: Labor and Poverty, in the context of Maranhão State in articulation with regional and national realities. The main conclusion is that work and poverty are part of the historical and contemporary reality and that, despite of the possibility of changes coming from the State intervention, structural determinations and the actual conservative, social and historical context tends to impose considerable limits and challenges to make changes in the outlined context.